2004
DOI: 10.1016/j.tws.2004.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Deflections of highly inflated fabric tubes

Abstract: Inflatable beams made of modern textile materials with important mechanical characteristics can be inflated at high pressure. The aim of the paper is to present experimental, analytical and numerical results on the deflections of highly inflated fabric tubes submitted to bending loads. Experiments are displayed and we show that tube behaviour looks like that of inflatable panels (Thin-Walled Struct. 40 (2002) 523-536). Equilibrium equations are once again written in the deformed state to take into account the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(38 citation statements)
references
References 6 publications
3
33
0
Order By: Relevance
“…Main et al [3,4] made experiments on a cantilever and improved Comer's theory. More recently, Wielgosz and Thomas [5,6] have derived analytical solutions for inflated panels and tubes by using the Timoshenko kinematics and by writing the equilibrium equations in the deformed state of the beam in order to take into account the follower force effect of the internal pressure. They have obtained new expressions for the deflection and shown that the limit load is proportional to the applied pressure and that the deflections are inversely proportional to the material properties of the fabrics and to the applied pressure, thus improving Fichter's theory.…”
Section: Introductionmentioning
confidence: 99%
“…Main et al [3,4] made experiments on a cantilever and improved Comer's theory. More recently, Wielgosz and Thomas [5,6] have derived analytical solutions for inflated panels and tubes by using the Timoshenko kinematics and by writing the equilibrium equations in the deformed state of the beam in order to take into account the follower force effect of the internal pressure. They have obtained new expressions for the deflection and shown that the limit load is proportional to the applied pressure and that the deflections are inversely proportional to the material properties of the fabrics and to the applied pressure, thus improving Fichter's theory.…”
Section: Introductionmentioning
confidence: 99%
“…(1) are 27 and 41 Nm when considering a 50 mm boom at 69 and 103 kNm -2 respectively. Other stiffening effects must also be considered having been observed in highly inflated structures [16] and analysed in detail by Davids (2008). This is caused by work done by pressure from deformation induced volume changes, such as boom bending and shearing, and can increase the structural capacity of inflatable booms beyond the 2M W limit predicted by Comer and Levy.…”
Section: Experimental Setup and Developmentmentioning
confidence: 99%
“…However there was increasing divergence between results at increased pressures. Experimental research by Thomas and Wielgosz (2004) [16] has shown highly inflated booms create pressure stiffening effects affecting the load-deflection response and increasing the load capacity of booms. Davids (2007) [17] formalised this by incorporating work done by pressure from deformation induced volume changes to a Timoshenko finite beam element model.…”
Section: Introductionmentioning
confidence: 99%
“…Fichter [7] published a paper in which the internal pressure appears in the deflection expression based on the minimization of total potential energy. By taking into account the deformed state of the beam, Wielgosz & Thomas [8,9] gave analytical expressions for inflated beams and panels using Timoshenko beam theory. In their approach, the force generated by internal pressure was treated as a follower force, which accounted for pressure stiffening effects.…”
Section: Introductionmentioning
confidence: 99%